Faktor-faktor yang Mempengaruhi Kemunculan Gangguan Depresi pada Penderita Cedera Tulang Belakang di Rumah Sakit Orthopedi Prof. Dr. R. Soeharso Surakarta - Wulan, Untari Retno, Dr. Nisa Rachmah N. A., M.Si., Psikolog, Setia Asyanti, S.Psi., M.Si., Psikolog (2016)
Abstract. Depression is a general consequence that sustained by patients who suffered from spinal cord injury through many factors triggering the emergence. The aim of this research are: (1) finding the factor that affecting the emerge of depression in patients with spinal cord injury, (2) understanding the psychological dynamics of the emergence of depression in patients with spinal cord injury (3) composing a program as a prevention of depression in patients with spinal cord injury. The research informant consists of four spinal cord injury patients as main informant who categorize as severe depression, moderate, mild, and not depression, also four caregiver as a proponent informant. The data collection is done by using BDI (Beck Depression Inventory), deep interview and observation. The presence or absence of depression associated with the healing process is done. The result shows internal factor of the biological realm associated physical disorder; psychologically related to introverted personality and arise of negative thoughts; spiritual realm emerging awareness to draw closer to Allah SWT with remorse for disobedience during the time; external factors of the social aspects related to the relationship with the families and communities who disturbed may trigger the emergence of depression in patients with spinal cord injury. Treatment needs to do thoroughly well from biological, psychological, social and spiritual (biopsychosocial spiritual) implied in holistic interventions.